Effectiveness, Challenges, and Opportunities of Human Resource Information Systems in Canning Companies in General Santos City - Rogan Jr., Genaro; Sanido, Kenneth (JPAIR Multidisciplinary Research, 2026)
Human Resource Information Systems (HRIS) are increasingly vital to strategic human resource management because they improve information handling, service delivery, and managerial decision support. Using a descriptive-correlational design, this study examined HRIS effectiveness, implementation challenges, and associated opportunities among 75 HR personnel, department managers, and HRIS end-users from five canning companies in General Santos City, Philippines. Data were gathered through a validated, closed-ended questionnaire and analyzed using frequency counts, percentages, weighted means, the Kolmogorov-Smirnov normality test, and Pearson's r correlation at the 0.05 level of significance. Results showed that HRIS implementation was highly effective (M = 4.03), especially in operational efficiency, data security, workload reduction, and overall HR operations. Challenges were moderate (M = 3.19), with data security concerns, financial limitations, training needs, and system customization emerging as the most visible constraints. Opportunities remained high (M = 3.85), particularly in centralized data management, automation, compliance, analytics, and strategic HR alignment. The relationship between HRIS effectiveness and opportunities was very strong and significant (r = 0.8369, p = 0.0000), whereas the relationship between challenges and opportunities was weak and not significant (r = -0.1492, p = 0.2020). The findings indicate that observable system effectiveness, more than implementation barriers, drives strategic opportunity. For HR managers, this underscores the value of prioritizing usable, secure, and integrated HRIS functions to expand organizational benefits.
Keywords: Human resource management; human resource information system; descriptive-correlational design; canning industry; General Santos City; Philippines